2012
DOI: 10.1111/eea.12011
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of a thrips‐transmitted Tospovirus on the preference and fitness of its vector, Frankliniella fusca

Abstract: Phytoviruses including tospoviruses are known to affect the behavior and fitness of their vectors both positively and negatively. In this study, we investigated the effects of Tomato spotted wilt virus (TSWV) (family Bunyaviridae, genus Tospovirus) infection on the fitness and feeding ability of tobacco thrips, Frankliniella fusca (Hinds) (Thysanoptera: Thripidae) using peanut, Arachis hypogaea L. (Fabaceae), as a host. Potentially viruliferous F. fusca laid more eggs than non‐viruliferous F. fusca. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 71 publications
1
58
0
Order By: Relevance
“…Our work and other recent findings [24], [26] suggest that the transmission mechanisms shape pathogens effects on host-vector interactions. We conclude that TYLCV, a circulative phloem-restricted begomovirus, has evolved to manipulate the settling, probing and feeding behavior of its vector, B. tabaci in a manner that facilitates its own transmission.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our work and other recent findings [24], [26] suggest that the transmission mechanisms shape pathogens effects on host-vector interactions. We conclude that TYLCV, a circulative phloem-restricted begomovirus, has evolved to manipulate the settling, probing and feeding behavior of its vector, B. tabaci in a manner that facilitates its own transmission.…”
Section: Discussionsupporting
confidence: 82%
“…Relatively little research has explored solely the direct effects of plant pathogens on their vectors when they are ingested and circulate through their body. In fact, most of the studies have concentrated on the indirect effects mediated by the plant when a virus induces changes in vector performance and behavior or in the preference for its plant host after infection [19][23], or the mixed effects (direct plus indirect effects) [24], [25]. Evaluating the indirect effects, from the pathogen stand point, the virus will benefit when the attractiveness of the infected host plant is maximum until the vector lands and probes on the plant.…”
Section: Introductionmentioning
confidence: 99%
“…The settling, probing, and feeding behavior of whiteflies transmitting Tomato leaf curl virus has also been shown to be conditional on the infection status of tobacco and whether the vector was viruliferous (Moreno-Delafuente et al 2013). Similarly, other recent studies demonstrated that feeding behavior or preference of thrips vectors of Tospoviruses change after virus acquisition by the vector (Stafford et al 2011, Shrestha et al 2012). These conditional preferences would be expected to lead to increased virus spread and suggest that some viruses may have evolved to manipulate the settling, probing and feeding behavior of their vectors to enhance transmission, although the mechanisms responsible have not been identified.…”
Section: Introductionmentioning
confidence: 92%
“…, Shrestha et al. ). These conditional preferences would be expected to lead to increased virus spread and suggest that some viruses may have evolved to manipulate the settling, probing and feeding behavior of their vectors to enhance transmission, although the mechanisms responsible have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…To efficiently transmit from plant to plant, viruses induce chemical and physical changes in the host, affecting vector-host interactions (Eigenbrode et al 2002;Hurd 2003;Belliure et al 2005). In addition, plant viruses can modify the feeding preferences or feeding behaviour of their insect vector to enhance transmission efficiency and spread (Stafford et al 2011;Ingwell et al 2012;Shrestha et al 2012;Moreno-Delafuente et al 2013).…”
Section: Introductionmentioning
confidence: 99%